Increased prenatal maternal investment reduces inbreeding depression in offspring. Issue 1860 (16th August 2017) - Ihle, Kate E.; Hutter, Pascale; Tschirren, Barbara
Abstract : Inbreeding depression refers to the reduction of fitness that results from matings between relatives. Evidence for reduced fitness in inbred individuals is widespread, but the strength of inbreeding depression varies widely both within and among taxa. Environmental conditions can mediate this variation in the strength of inbreeding depression, with environmental stress exacerbating the negative consequences of inbreeding. Parents can modify the environment experienced by offspring, and have thus the potential to mitigate the negative consequences of inbreeding. While such parental effects have recently been demonstrated during the postnatal period, the role of prenatal parental effects in influencing the expression of inbreeding depression remains unexplored. To address this gap, we performed matings between full-sibs or unrelated individuals in replicated lines of Japanese quail ( Coturnix japonica ) experimentally selected for high and low maternal egg provisioning. We show that in the low maternal investment lines hatching success was strongly reduced when parents were related. In the high maternal investment lines, however, this negative effect of inbreeding on hatching success was absent, demonstrating that prenatal maternal provisioning can alleviate the negative fitness consequences of inbreeding.